Toward a discursive marketplace of ideas: Reimaging the marketplace metaphor in the era of social media, fake news, and artificial intelligence. Issue 1 (3rd July 2018) - Schroeder, Jared
ABSTRACT: The marketplace of ideas metaphor remains one of the Supreme Court's most enduring tools for communicating understandings regarding freedom of expression. For nearly a century, justices from a variety of judicial philosophies, in several areas of First Amendment law, including commercial speech, defamation, and obscenity, have called upon the metaphor to help them convey what have ultimately become crucial interpretations regarding the Amendment's protections. Metaphors, however, do not have static meanings. In light of the important considerations of paradigmatic social and technological changes that have substantially altered the very nature of the marketplace of ideas in society, particularly in the era of social media, fake news, and artificially intelligent communicators, this essay examines how the marketplace metaphor can be both reinterpreted and reimagined to account for a substantially different twenty-first-century information environment while remaining faithful to its author's understandings about the nature of truth. To this end, this essay examines how Justice Oliver Wendell Holmes understood truth, considers differences between Enlightenment and discursive-based understandings regarding the flow of communication in democratic society, and explores how the Supreme Court has traditionally employed the metaphor. Finally, it proposes a revised conceptualization of the marketplace of ideas, ultimately labeled as the "discursive marketplace."